Competency Assessment Tool (CAT). The evaluation of an innovative competency-based assessment experience in higher education. Issue 5 (19th October 2016) - Ion, Georgeta; Cano, Elena; Cabrera, Nati
Abstract : This article examines an innovation in teaching-learning and assessment processes through the use of a platform called the Competency Assessment Tool (CAT). It allows for the tracking of student blogs with the objective of improving self-reflective processes and providing feedback. The experiment was carried out in six universities in Catalonia, Spain, and involved seven different subjects. The CAT platform and its features related to the acquisition of competencies are presented, as are users' opinions on the metacognitive and feedback processes provided by the tool. The methods used were questionnaires received by students and teachers. Results show a high level of satisfaction for all those involved and emphasise that student participation in the assessment process increases their awareness of the teaching-learning process through self-regulation procedures. The most significant result is related to the use of electronic tools as an appraisal instrument and their enhancement of competency-based assessment.